1981
DOI: 10.1177/154079698200600406
|View full text |Cite
|
Sign up to set email alerts
|

Toward Generalization of Appropriate Leisure and Social Behavior in Severely Handicapped Youth: Pinball Machine Use

Abstract: teacher of learning disabled students, Hanover County, Virginia. Article Descriptors electronic pinball; age-appropriate leisure; generalization; adolescent; severely handicapped; community-based trainingThis study demonstrated the acquisition and generalization into community settings of a chron ologically age-appropriate leisure skill with severe ly and profoundly mentally retarded adolescents. The skill involved operating an electronic pinball machine independently.The study evaluated the effects of an inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…Probe trials clearly revealed that the skills did not generalize to the natural environment until training was conducted there. Similar findings were reported by Hill, Wehman, and Horst (1982) regarding teaching severely handicapped students to use pinball machines as a leisure skill. Both of these studies reported generalization to new environments only after training in the natural environment was completed.…”
Section: Natural Vs Artificial Environmentssupporting
confidence: 91%
“…Probe trials clearly revealed that the skills did not generalize to the natural environment until training was conducted there. Similar findings were reported by Hill, Wehman, and Horst (1982) regarding teaching severely handicapped students to use pinball machines as a leisure skill. Both of these studies reported generalization to new environments only after training in the natural environment was completed.…”
Section: Natural Vs Artificial Environmentssupporting
confidence: 91%
“…Concurrent instructional scheduling provides the student additional structured practice and opportunities to experience a wider range of stimuli managed in a controlled setting within the classroom, while also providing the student experience with naturally occurring antecedents, consequences, and criteria when in the community (Ford & Mirenda, 1984;Nietupski, Hamre-Nietupski, Clancy, & Veerhusen, 1986). Scheduling simulated instruction and community-based instruction (CBI) on the same day is effective and efficient for students acquiring, maintaining, and generalizing community skills (Branham et al, 1999;Collins, Stinson, & Land, 1993); functional/vocational skills (Cihak et al, 2004;Nietupski, Clancy, et al, 1985); and leisure skills (Hill, Wehman, & Horst, 1982). Bates, Cuvo, Miner, and Korbeck (2001) noted that substantial evidence supports concurrent programming and that "research is needed to examine various types of simulations in combination with community assessment and/or training opportunities for teaching functional living skills" (p. 114).…”
mentioning
confidence: 98%
“…These illustrations include community mobility, recreation/leisure, and vocational skills (Bates, Renzaglia, & Clees, 1980;Hill, Wehman, & Horst, 1982). These illustrations have demonstrated that "potential" is at least in part a function of the quality of educational experiences provided, rather than solely of presumed innate capacity.…”
Section: Applicability To Low Functioning Multiply Hand Icapped Studmentioning
confidence: 95%